Understanding the Barriers to Crystal Growth:Dynamical Simulation of the Dissolution and Growth of Urea from Aqueous Solution - Piana, Stefano; Gale, Julian (The American Chemical Society, 2005)
Both the dissolution and growth of a molecular crystalline material, urea, has been studied using dynamical atomistic simulation. The kinetic steps of dissolution and growth are clearly identified, and the activation energies for each possible step are calculated. Our molecular dynamics simulations indicate that crystal growth on the [001] face is characterized by a nucleation and growth mechanism. Nucleation on teh [001] urea crystal faace is predicted to occur at a very high rate, followed by rapid propagation of the steps. The rate-limiting step for crystallization is actually found to be the removal of surface defects, rather than the initial formation of the next surface layer. Through kinetic Monte Carlo modeling of the surface growth, it is found that this crystal face evolves via a rough surface topography, rather than a clean layer-by-layer mechanism.